Epidemiological profile of Covid-19 in the State of Rio Grande do Norte: analysis from the age range of positive cases (Research, Society and Development, 2020)
Objective: to describe the epidemiological profile of COVID-19 and analyze from the age group, based on figures provided by the Rio Grande do Norte Department of Public Health. Methodology: ecological, descriptive study, developed through the analysis of confirmed cases of COVID-19 in the state of Rio Grande do Norte, until October 3, 2020; and its main characteristics according to the age group. Results: A higher prevalence of cases was observed in the metropolitan region, where the capital Natal is located; the groups of highest notification were people up to 59 years old, females and individuals of mixed race/color. Cough was presented as the most common symptom that requires attention and encourages the patient to seek medical attention. The chronic heart disease comorbidity prevailed, even though most of those confirmed did not present any comorbidity. Conclusion: The present study may be useful to support and better target actions to combat COVID-19, not only locally, but also in regions that may have similar sociodemographic characteristics.